2021
DOI: 10.1016/j.ribaf.2021.101400
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, stock market and sectoral contagion in US: a time-frequency analysis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 19 publications
3
28
0
Order By: Relevance
“…The authors point that international information asymmetry can drive the removal of resources from investors across countries. Matos et al (2021) support the presence of this movement in the beginning of the coronavirus pandemic.…”
Section: Literature Reviewsupporting
confidence: 55%
See 1 more Smart Citation
“…The authors point that international information asymmetry can drive the removal of resources from investors across countries. Matos et al (2021) support the presence of this movement in the beginning of the coronavirus pandemic.…”
Section: Literature Reviewsupporting
confidence: 55%
“…Fortunately, there is already some literature on contagion between sectors, and specifically the banking sector, during this pandemic. Matos et al (2021) propose assessing the conditional relationship in the time-frequency domain between the return on S&P 500 and the cases or deaths by COVID-19 in Hubei, China, countries with record deaths and the world, for the period from 29 January to 30 June 2020. They find that short-term cycles of deaths in Italy in the first days of March, and soon afterwards, cycles of deaths in the world can lead out-of-phase US stock market.…”
Section: Introductionmentioning
confidence: 99%
“…A fast-growing body of research on the pandemic effects on financial markets has emerged. Matos et al (2021) demonstrated that the US stock market was negatively correlated to the cycles of deaths in Italy and the world at the beginning of the pandemic. Albulescu (2020) showed that COVID-19 caused a significant increase in the US stock market volatility.…”
Section: Introductionmentioning
confidence: 99%
“…As the extended usage of wavelet transformation, wavelet coherence and phase difference can be utilized to recognize whether two time series are quantitatively connected by a certain correlation even causality relationship. Matos et al (28) assessed the conditional relationship in the time-frequency domain between the return on SPX 500 and COVID-19 confirmed cases and deaths, by partial coherencies, phase-difference diagrams, and gains, and found the usefulness of low frequency cycles of U.S. stock market index in anticipating the cycles of deaths in an anti-phasic way. Su et al (2019) utilized continuous wavelet analysis and aimed to assess whether the causality of geopolitical risk, oil prices, and financial liquidity supported the monetary equilibrium model in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%